DuoMab: a novel CrossMab-based IgG-derived antibody format for enhanced antibody-dependent cell-mediated cytotoxicity. Issue 8 (17th November 2019) - Sustmann, Claudio; Dickopf, Steffen; Regula, Jörg T.; Kettenberger, Hubert; Mølhøj, Michael; Gassner, Christian; Weininger, Diana; Fenn, Sebastian; Manigold, Tobias; Kling, Lothar; Künkele, Klaus-Peter; Schwaiger, Manfred; et al.
ABSTRACT: High specificity accompanied with the ability to recruit immune cells has made recombinant therapeutic antibodies an integral part of drug development. Here we present a generic approach to generate two novel IgG-derived antibody formats that are based on a modification of the CrossMab technology. MoAbs harbor two heavy chains (HCs) resulting in one binding entity and one fragment crystallizable region (Fc), whereas DuoMabs are composed of four HCs harboring two binding entities and two Fc regions linked at a disulfide-bridged hinge. The latter bivalent format is characterized by avidity-enhanced target cell binding while simultaneously increasing the 'Fc-load' on the surface. DuoMabs were shown to be producible in high yield and purity and bind to surface cells with affinities comparable to IgGs. The increased Fc load directed at the surface of target cells by DuoMabs modulates their antibody-dependent cell-mediated cytotoxicity competency toward target cells, making them attractive for applications that require or are modulated by FcR interactions.